Gambaran School Well Being Pada Siswa SMA - Ika Amalia (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2020)
This study aims to illustrate how the well-being of schools among high school students by taking a sample of students at SMPN 1 Nisam, North Aceh District, Aceh Province. This study uses data collection techniques in the form of semi-structured interviews. The results showed that the description of school welfare experienced by students at SMAN 1 Nisam, North Aceh district was very high. A very prominent dimension in the well-being of schools at focus study is social relations (loving). The results of the study are recommended as input to consideration for schools in creating a more conducive learning climate that leads to better school conditions.